Attending to the heart is associated with posterior alpha band increase and a reduction in sensitivity to concurrent visual stimuli. (31st May 2017) - Villena‐González, Mario; Moënne‐Loccoz, Cristóbal; Lagos, Rodrigo A.; Alliende, Luz M.; Billeke, Pablo; Aboitiz, Francisco; López, Vladimir; Cosmelli, Diego
Abstract: Attentional mechanisms have been studied mostly in specific sensory domains, such as auditory, visuospatial, or tactile modalities. In contrast, attention to internal interoceptive visceral targets has only recently begun to be studied, despite its potential importance in emotion, empathy, and self‐awareness. Here, we studied the effects of shifting attention to the heart using a cue‐target detection paradigm during continuous EEG recordings. Subjects were instructed to count either a series of visual stimuli (visual condition) or their own heartbeats (heart condition). Visual checkerboard stimuli were used as attentional probes throughout the task. Consistent with previous findings, attention modulated the amplitude of the heartbeat‐evoked potentials. Directing attention to the heart significantly reduced the visual P1/N1 amplitude evoked by the attentional probe. ERPs locked to the attention‐directing cue revealed a novel frontal positivity around 300 ms postcue. Finally, spectral power in the alpha band over parieto‐occipital regions was higher while attending to the heart—when compared to the visual task—and correlated with subject's performance in the interoceptive task. These results are consistent with a shared, resource‐based attentional mechanism whereby allocating attention to bodily signals can affect early responses to visual stimuli.